Director reorientation in a cell with time-dependent anchoring due to adsorption/desorption of LC molecules - Romanenko, A.; Pinkevich, I.; Reshetnyak, V.; Dozov, I.; Stoenescu, D. (Functional Materials, 2005)
Influence of adsorption/desorption process of nematic molecules at the nematic cell substrate on the nematic crystal director evolution in time that is due to external magnetic field has been considered. It is shown that boundary conditions at the cell surface evolve in accordance with the distribution of nematic molecular orientation in the cell bulk. During the time evolution, the orientation distribution function of molecules adsorbed at the cell substrate can exhibit two maxima. By switching off the magnetic field at the suitable moment, it is possible obtain a bistable nematic system.